Echinoderm radial glia in adult cell renewal, indeterminate growth, and regeneration - Mashanov, Vladimir; Ademiluyi, Soji; Jacob Machado, Denis; Reid, Robert; Janies, Daniel (Frontiers in Neural Circuits, 2023)
Echinoderms are a phylum of marine deterostomes with a range of interesting biological features.One remarkable ability is their impressive, including an outstanding capacity to regenerate most of their adult tissues, including the central nervous system (CNS). The research community has accumulated data that demonstrates that, in spite of the pentaradial adult body plan, echinoderms share deep similarities with their bilateral sister taxa such as hemichordates and chordates. Some of the new data reveal the unexpected complexity of the nervous system in echinoderms. In terms of the cellular architecture, one of the traits that is shared between the CNS of echinoderms and chordates is the presence of radial glia. In chordates, these cells act as the main progenitor population in CNS development. In mammals, radial glia are spent in embryogenesis and are no longer present in adults, being replaced with other neural cell types. In non-mammalian chordates, they are still detected in the mature CNS along with other types of glia. In echinoderms, radial glia also persist into the adulthood, but unlike in chordates, it is the only known glial cell type that is present in the fully developed CNS. The echinoderm radial glia is a multifunctional cell type.:Radial gliait forms the supporting scaffold of the neuroepithelium, exhibits secretory activity, clears up dying or damaged cells by phagocytosis, and, most importantly, acts as a major progenitor cell population. The latter function is critical for the outstanding developmental plasticity of the adult echinoderm CNS, including physiological cell turnover, indeterminate growth, and a remarkable capacity to regenerate major parts following autotomy or traumatic injury. In thisThe present review we summarizes the current knowledge on the organization and function of the echinoderm radial glia, with athe primary focus on the role of this cell type in adult neurogenesis.